La chasse aux fantômes sur YouTube. Approche ethnographique et quali-quantitative des commentaires des vidéos - Fanny Georges (Communiquer)
To what extent can contemporary culture be observed on the internet? This article proposes to analyze the comments on YouTube of ghost hunting videos in a quali-quantitative approach, by mobilizing the theoretical framework of Yuri Lotman’s cultural semiotics. Drawing on public data from four YouTube channels featuring paranormal investigations in haunted places, the analysis highlights the social and technical injunctions (social expectations, algorithm), the common contributors to several chains, and the social function of the comments. The results show that the paranormal web is a place for the construction of an experiential and game-like updating of the ancestral culture of communication with spirits. Withdrawn from any quest for a single and indivisible truth, digital ghost hunters and their followers invest digital technologies as new mediums for a spiritual communication embodied as a concrete experience of physics and electromagnetic fields.